The Use of the Syllable Method to Improve Early Reading Skills of Second Grade Students at SD Panyabungan - Nur Kholijah; Rica Umrina Lubis; Ali Yusron (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: This study was motivated by the low early reading ability of second-grade students at SD Negeri 088 Panyabungan. The purpose of this research is to describe the implementation of the syllable (syllabic) method in improving students’ early reading skills. This study employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The research subjects were 27 second-grade students. Data were collected through classroom observations and reading ability tests. The data were analyzed using descriptive quantitative analysis to identify improvements in students’ learning outcomes across the research cycles. The results showed that the implementation of the syllable method significantly improved students’ early reading ability. In the pre-cycle stage, the average score was 61.11 with a learning mastery level of 44% (12 students). After the implementation of Cycle I, the average score increased to 74.6 with a mastery level of 67% (18 students). Improvements in the learning process during Cycle II resulted in a more significant increase, with the average score reaching 80 and the mastery level rising to 89% (24 students). These findings indicate that the syllable method is effective in improving the early reading ability of second-grade students at SD Negeri 088 Panyabungan.Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya kemampuan membaca permulaan siswa kelas II di SD Negeri 088 Panyabungan. Penelitian ini bertujuan untuk mendeskripsikan penerapan metode silabel dalam meningkatkan kemampuan membaca permulaan siswa. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang mengacu pada model Kemmis dan McTaggart, yang dilaksanakan dalam dua siklus. Setiap siklus terdiri atas empat tahap, yaitu perencanaan (planning), pelaksanaan tindakan (acting), observasi (observing), dan refleksi (reflecting). Subjek penelitian berjumlah 27 siswa kelas II. Teknik pengumpulan data dilakukan melalui observasi dan tes kemampuan membaca, sedangkan analisis data menggunakan analisis deskriptif kuantitatif untuk melihat peningkatan hasil belajar siswa pada setiap siklus. Hasil penelitian menunjukkan bahwa penerapan metode silabel mampu meningkatkan kemampuan membaca permulaan siswa. Pada tahap pra-siklus, nilai rata-rata siswa sebesar 61,11 dengan tingkat ketuntasan belajar 44% (12 siswa). Setelah penerapan tindakan pada siklus I, nilai rata-rata meningkat menjadi 74,6 dengan ketuntasan belajar 67% (18 siswa). Perbaikan pembelajaran pada siklus II menunjukkan peningkatan yang lebih signifikan dengan nilai rata-rata mencapai 80 dan ketuntasan belajar 89% (24 siswa). Hasil tersebut menunjukkan bahwa penggunaan metode silabel efektif dalam meningkatkan kemampuan membaca permulaan siswa kelas II SD Negeri 088 Panyabungan.